2012
DOI: 10.1186/1476-511x-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Dietary resveratrol increases the expression of hepatic 7α-hydroxylase and ameliorates hypercholesterolemia in high-fat fed C57BL/6J mice

Abstract: BackgroundResveratrol (RSV), a naturally occurring polyphenolic stilbenoid, is known to possess potent anti-atherogenic properties; however, the effect of RSV on hypercholesterolemia is not fully understood. We hypothesized that RSV decreases blood cholesterol levels through the activation of cholesterol 7α-hydroxylase (CYP7A1)-mediated bile acid synthetic pathway pathways in vitro and in vivo.MethodsIn this study, we evaluated body weight, serum lipid concentrations, hepatic lipid content and the size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 27 publications
5
48
1
Order By: Relevance
“…Bile acids genesis contributes to the elimination of cholesterol from plasma. Chen et al (2012) demonstrated increased CYP7A1 mRNA transcription, protein production and activity. In particular, CYP7A1 increased liver X receptor alpha (LXRa) activation.…”
Section: Nutraceutical Effects On Dyslipidaemia: Action Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bile acids genesis contributes to the elimination of cholesterol from plasma. Chen et al (2012) demonstrated increased CYP7A1 mRNA transcription, protein production and activity. In particular, CYP7A1 increased liver X receptor alpha (LXRa) activation.…”
Section: Nutraceutical Effects On Dyslipidaemia: Action Mechanismsmentioning
confidence: 99%
“…The benefits from red wine consumption (i.e., the ''French paradox'') (Renaud & de Lorgeril, 1992) higher concentrations of resveratrol are in red wine (0.847 mg/100 g) and itadori tea (0.974 mg/100 g), followed by wine, grapes, grape juice and peanut butter (range from 0.08 to 0.547 mg/100 g) and peanuts, pistachios and berries (0.01 mg/100 g). Chen et al (2012) hypothesised the role of resveratrol in counteracting hypercholesterolaemia. They fed mice a hypercholesterolaemic diet and resveratrol (200 mg/kg/day) for 8 weeks, observing a reduction in main serum lipid parameters.…”
Section: Nutraceutical Effects On Dyslipidaemia: Action Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary selenium and/or GPX1 production (9) affected the functional expression of important proteins involved in gluconeogenesis [phosphoenolpyruvate carboxykinase (PEPCK)] and glycolysis [glucokinase (GK)] (10), insulin signaling [insulin receptor (INSR), insulin receptor substrate 1 (IRS1), and v-akt murine thymoma viral oncogene homolog 2 (AKT2)], and lipid metabolism (11) [sterol regulatory element binding protein (SREBP) 1 and SREBP2, acetyl-CoA carboxylase 1 (ACC1); cholesterol 7a-hydroxylase (CYP7A1), PPARG, fatty acid synthase (FASN), and tumor suppressor p53 (P53)] (12)(13)(14)(15)(16)(17). Alterations of these factors were associated with expressions of 12 selenoproteins (1,3,5,9,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…It mediates the conversion of cholesterol in 7α-hydroxycholesterol and, subsequently, in cholic acid. Bile acids genesis contributes to the elimination of cholesterol from plasma [25].…”
Section: Nutraceuticals For Dyslipidemiamentioning
confidence: 99%